Prospective trial to evaluate the prognostic value of different nutritional assessment scores in pancreatic surgery (NURIMAS Pancreas) - Probst, Pascal; Haller, Sebastian; Bruckner, Thomas; Ulrich, Alexis; Strobel, Oliver; Hackert, Thilo; Diener, Markus K.; Büchler, Markus W.; Knebel, Phillip (The British journal of surgery, 2017)
Background: Preoperative nutritional status has an impact on patients' clinical outcome. For pancreatic surgery, however, it is unclear which nutritional assessment scores adequately assess malnutrition associated with postoperative outcome. Methods Patients scheduled for elective pancreatic surgery at the University of Heidelberg were screened for eligibility. Twelve nutritional assessment scores were calculated before operation, and patients were categorized as either at risk or not at risk for malnutrition by each score. The postoperative course was monitored prospectively by assessors blinded to the nutritional status. The primary endpoint was major complications evaluated for each score in a multivariable analysis corrected for known risk factors in pancreatic surgery. Results Overall, 279 patients were analysed. A major complication occurred in 61 patients (21·9 per cent). The proportion of malnourished patients differed greatly among the scores, from 1·1 per cent (Nutritional Risk Index) to 79·6 per cent (Nutritional Risk Classification). In the multivariable analysis, only raised amylase level in drainage fluid on postoperative day 1 (odds ratio (OR) 4·91, 95 per cent c.i. 1·10 to 21·84; P = 0·037) and age (OR 1·05, 1·02 to 1·09; P = 0·005) were significantly associated with major complications; none of the scores was associated with, or predicted, postoperative complications. Conclusion None of the nutritional assessment scores defined malnutrition relevant to complications after pancreatic surgery and these scores may thus be abandoned.